Türkiyenin Kıbrıs’a müdahale kararı alması - Ölmez, Nagihan (My University, 2024)
Kıbrıs’ta Türklerin maruz kaldığı baskı ve zulümler karşısında Türk Silahlı Kuvvetleri 20 Temmuz 1974 tarihinde adaya ilk askeri müdahaleyi gerçekleştirmiştir. Kıbrıs’taki anayasal düzeni sağlamak amacıyla yapılan Kıbrıs Barış Harekâtı, Garanti Antlaşması’nın verdiği yetkiye dayanmakla birlikte uygulanması en zor harekatlardan biri olmuştur. Bu çalışmada Türkiye’nin Kıbrıs’a müdahale kararının Türkiye tarafından nasıl alındığı, Kıbrıs Barış Harekatı’na giden süreçte TBMM’de, Bakanlar Kurulu’nda MGK’da ve Cumhuriyet Senatosu’nda nasıl kararlar alındığı ve neler konuşulduğu tezin ana konusunu oluşturmaktadır. Bu çalışmada Türk ve Kıbrıs gazete haberleriyle birlikte, karar almada etkili olan TBMM kararları, Bakanlar Kurulu kararları, MGK kararları ve Cumhuriyet Senatosu kararları ele alınacaktır.

In the face of the pressure and oppression suffered by the Turks in Cyprus, the Turkish Armed Forces carried out the first military intervention on the island on July 20, 1974. The Cyprus Peace Operation, which was carried out to ensure the constitution alorder in Cyprus, was one of the most difficult operations to implement, although it was based on the authority given by the Treaty of Guarantee. In this study, the main subject of the thesis is how Turkey's decision to intervene in Cyprus was taken by Turkey, what decisions were made and what was discussed in the Turkish Grand National Assembly, the Council of Ministers, the MGK and the Senate of the Republic in the process leading up to the Cyprus Peace Operation. In this study, along with Turkish and Cypriot newspapernews, the decisions of the Grand National Assembly of Turkey, the decisions of the Council of Ministers, the decisions of the National Security Council and the decisions of the Senate of the Republic, which are effective in decision-making, will be discussed.
Keywords: 1974; Cyprus; Cyprus crisis, 1974-; Cyprus Island; Cyprus Peace Operation; History; Kıbrıs; Kıbrıs Adası; Kıbrıs Barış Harekâtı; Kıbrıs krizi, 1974-; Tarih; Turkey; Türkiye